Corrupted - Scottoline, Lisa; Burton, Kate (New York : Macmillan Audio, 2015)
Bennie Rosato, the founder of the Rosato & DiNunzio law firm, hides her big heart beneath her tough-as-nails exterior--and she doesn't like to fail. Now a case from her past shows her how differently things might have turned out. Thirteen years ago, she took on Jason Lefkavick, a twelve-year-old boy who was sent to a juvenile detention center after fighting a class bully. Bennie couldn't free Jason, and to this day it's the case that haunts her. Jason has grown up in and out of juvenile prison, and his adulthood hasn't been any easier. Bennie no longer represents those accused of murder, but when Jason's indicted for killing the same bully he fought with as a kid, she sees no choice but to represent him.
Keywords: Women lawyers -- Fiction; Murder -- Fiction -- Investigation; Audiobooks; Detective and mystery fiction